PENERAPAN LEAN MANUFACTURING UNTUK MENGURANGI WASTE PADA PROSES PRODUKSI (TIANG POST) PRODUK GUARDRAIL DI PT. XXX - Permana, Nanda; Pujani, Vera (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2020)
This study aims to apply Lean Manufacturing to Reduce Waste in the Production Process (Pole Posh) of Guardrail Products. The object of research is the result of the production of posh pole PT. XXX. The approach used in this research is descriptive qualitative approach. Descriptive qualitative research is meant about understanding phenomena that occur in the object of research. The snowball sampling method which is a sampling technique based on interviews or correspondence by asking for information from the first sample to get the next sample until research needs are met, in this study the snowball sampling method is used to select the correspondence at PT. XXX to find out the type of waste that occurs during production process in order to conduct further analysis in this study. Data collection techniques with primary data and secondary data, while data collection techniques with secondary data, observation and interviews. Data analysis technique used Value Stream Mapping